Membentuk Identitas Diri Digital di Era Media Sosial: Studi Kualitatif terhadap Guru - Firdauza, Intan Ayu Lasmana; Chusniyah, Tutut (Flourishing Journal, 2025)
The development of social media has transformed how individuals build and present their identities, including within professional contexts such as teaching. This study aims to explore how teachers construct and manage their digital identity through platforms like LinkedIn and personal social media such as Instagram and TikTok. Using a qualitative approach with a phenomenological method, this study involved three active teachers selected purposively. Data were collected through in-depth interviews and analyzed using a phenomenological data analysis technique. The findings show that teachers use LinkedIn to build a formal professional image, while Instagram and TikTok serve as spaces to express more casual and personal aspects of themselves. Strategies such as privacy settings, content selection, and separating personal and professional spheres are key to adjusting their identity to the social norms of each platform. Although teachers did not feel pressured, they demonstrated strong awareness of maintaining a professional image in digital spaces. This study concludes that teachers shape their digital identity consciously, strategically, and adaptively according to the social context of each social media platform. AbstrakPerkembangan media sosial telah mengubah cara individu membangun dan menampilkan identitas diri, termasuk dalam konteks profesional seperti profesi guru. Penelitian ini bertujuan untuk mengeksplorasi bagaimana guru membentuk dan mengelola identitas mereka melalui platform LinkedIn dan media sosial pribadi seperti Instagram dan TikTok. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologis dan melibatkan tiga guru aktif yang dipilih secara purposif. Data dikumpulkan melalui wawancara mendalam dan dianalisis dengan teknik analisis data fenomenologis. Hasil penelitian menunjukkan bahwa guru menggunakan LinkedIn untuk membangun citra profesional yang formal, sedangkan Instagram dan TikTok dimanfaatkan sebagai ruang untuk mengekspresikan sisi pribadi yang lebih santai. Strategi seperti pengaturan privasi, pemilihan konten, serta pemisahan antara kehidupan pribadi dan profesional menjadi cara utama dalam menyesuaikan identitas dengan norma sosial di masing-masing platform. Meskipun para guru tidak merasa tertekan, mereka tetap menunjukkan kesadaran tinggi dalam menjaga citra profesional di ruang digital. Penelitian ini menyimpulkan bahwa identitas digital guru dibentuk secara sadar, strategis, dan adaptif sesuai dengan konteks sosial dari setiap platform media sosial.